Agribusiness Enterpreneurial Strategies during Financialization Era. A case Study: El Tejar - Sosa Varrotti, Andrea Patricia; Frederico, Samuel [UNESP] (Univ Nacl La Plata, Fac Humanidades & Ciencias Educacion, 2018)
In this article, we analyze a central aspect of Mercosur's agriculture financialization: the entrance of risk capital in this economic sector. Among the main actors in this process, we can find private equity firms and the agribusiness mega-companies on which they invest. Using a qualitative-quantitative approach, we analyze one of the most accomplished examples of relationship between both types of companies thought a case study, the mega-company El Tejar -of Argentinean origin-, and its effects in terms of land and production grabbing in Argentina and Brazil.
Keywords: Financialization; Agribusiness; Mega-companies; Grabs; Mercosur; Brazil; Argentina; Lands